2016
DOI: 10.1101/gr.199430.115
|View full text |Cite
|
Sign up to set email alerts
|

Exome sequencing and CRISPR/Cas genome editing identify mutations of ZAK as a cause of limb defects in humans and mice

Abstract: The CRISPR/Cas technology enables targeted genome editing and the rapid generation of transgenic animal models for the study of human genetic disorders. Here we describe an autosomal recessive human disease in two unrelated families characterized by a split-foot defect, nail abnormalities of the hands, and hearing loss, due to mutations disrupting the SAM domain of the protein kinase ZAK. ZAK is a member of the MAPKKK family with no known role in limb development. We show that Zak is expressed in the developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
51
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 45 publications
(54 reference statements)
0
51
0
Order By: Relevance
“…The differences between human and mouse phenotypes are most likely a result of species differences, as well as enhancer redundancy in mice, which has been described in several recent studies. 3,43 Second, the CNV detection rate of 10% in patients with congenital limb malformation reported here might be slightly overestimated since our cohort is partially biased by the initial clinical selection. In this study, array CGH was used as a first screening test for all samples, but some samples were sent to us by collaborating laboratories only after candidate gene testing was performed and yielded no result.…”
Section: Discussionmentioning
confidence: 85%
“…The differences between human and mouse phenotypes are most likely a result of species differences, as well as enhancer redundancy in mice, which has been described in several recent studies. 3,43 Second, the CNV detection rate of 10% in patients with congenital limb malformation reported here might be slightly overestimated since our cohort is partially biased by the initial clinical selection. In this study, array CGH was used as a first screening test for all samples, but some samples were sent to us by collaborating laboratories only after candidate gene testing was performed and yielded no result.…”
Section: Discussionmentioning
confidence: 85%
“…ZAK is a direct target of Tp63, and the deletion of its SAM domain has been shown to be associated with downregulation of Tp63 in the developing limb bud (Figure 2). 42 The absence of split hands but the presence split feet in patients with ZAK mutations supports the control of ZAK by TP63 genes because the hindlimbs of the Tp63 KO mice are more severely affected than the forelimbs. 17,18 In addition, having split feet without split hands suggest the association of ZAK, PITX1, and TBX4 genes in the formation of feet.…”
Section: Zak and Shfmmentioning
confidence: 86%
“…The gene of interest in this study, ZAK, has been shown, in two consanguineous Pakistani pedigrees and in confirmatory animal models, to be relevant to SHFM with associated hearing loss. 7 The 38 patients selected for study in this cohort were screened for phenotypic match to patients with the reported pathogenic variant p.Phe368Cys in ZAK. All 38 patients in this cohort manifested the SHFM phenotype and had variable degrees of sensorineural hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…The authors generated a ZAK -/knockout mouse model which caused all mice to die during embryonic development. 7 Deletion of the SAM domain (which contains p.Phe368Cys) by CRISPR/Cas caused a hindlimb defect that was similar to the defect observed in mice with mutant Trp63, a known SHFM gene. 7 These studies demonstrate the relevance of the SAM domain within ZAK to SHFM.…”
Section: Introductionmentioning
confidence: 85%